Inherited retinal diseases: Therapeutics, clinical trials and end points—A review. (20th March 2021) - Georgiou, Michalis; Fujinami, Kaoru; Michaelides, Michel
Abstract: Inherited retinal diseases (IRDs) are a clinically and genetically heterogeneous group of disorders characterised by photoreceptor degeneration or dysfunction. These disorders typically present with severe vision loss that can be progressive, with disease onset ranging from congenital to late adulthood. The advances in genetics, retinal imaging and molecular biology, have conspired to create the ideal environment for establishing treatments for IRDs, with the first approved gene therapy and the commencement of multiple clinical trials. The scope of this review is to familiarise clinicians and scientists with the current management and the prospects for novel therapies for: (1) macular dystrophies, (2) cone and cone‐rod dystrophies, (3) cone dysfunction syndromes, (4) Leber congenital amaurosis, (5) rod‐cone dystrophies, (6) rod dysfunction syndromes and (7) chorioretinal dystrophies. We also briefly summarise the investigated end points for the ongoing trials.